2004
DOI: 10.1158/1078-0432.ccr-03-0139
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Plasma Hypermethylated DNA Markers of Undifferentiated Nasopharyngeal Carcinoma

Abstract: Purpose: Gene-specific methylation is common in primary undifferentiated nasopharyngeal carcinoma (NPC). DNA released from apoptotic or necrotic cell death including those aberrantly methylated promoter DNA of cancer cells is absorbed into the circulation as cell-free plasma DNA of the patient. This study aims at evaluation of the potential use of methylated gene promoter DNA as a serological tumor marker of primary and potentially salvageable local or nodal recurrent NPC.Experimental Design: The quantity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 32 publications
3
62
0
Order By: Relevance
“…Promoter hypermethylation of DAPK1 was also found to be restricted to the neuroendocrine component. Interestingly, the aberrant methylation of DAPK1 is considered an important epigenetic event in nasopharyngeal carcinomas [34] and has been evaluated as an early molecular marker of subclinical presence of this neoplasm [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Promoter hypermethylation of DAPK1 was also found to be restricted to the neuroendocrine component. Interestingly, the aberrant methylation of DAPK1 is considered an important epigenetic event in nasopharyngeal carcinomas [34] and has been evaluated as an early molecular marker of subclinical presence of this neoplasm [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that RASSF1A methylation is one of the most common aberrations so far identified in human cancers and that the loss of the functional protein may promote the development of many human tumors. Hypermethylation of the RASSF1A has been detected frequently in the tissues of different cancers [10][11][12][13][14][15][16][17], while in the body fluid, methylation of RASSF1A promoter has also been documented in 50% sputum and 84% serum from lung cancer [30], 35% urine from bladder cancer [15], 56-60% serum from breast caner [31][32][33], and 5% serum from undifferentiated nasopharyngeal carcinoma [34], which indicated the value of RASSF1A methylation in DNA for the early-stage diagnosis of tumors. Detection of methylated DNA has then been suggested as a potential biomarker for early detection of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing DAPk methylation status, it was possible to detect urinary bladder cancer from voided urine; head and neck cancer from saliva, mouth rinsing fluid or nasopharyngeal swab or serum; colon and breast cancer from serum; lung cancer from sputum, bronchial brush samples or serum; and cervix cancer from cervical cytology specimens. [51][52][53][54][55][56][57][58][59][60][61] Consequently, DAPk downregulation by methylation is a cancerspecific event, which may be used to specifically detect malignant cells.…”
Section: Dapk Family and Cancer: A Novel Tumor Suppressor Family Of Pmentioning
confidence: 99%